Shadows of glass - Tayler, Kassy
Wren, determined to keep the few surviving shiners safe with Pace's help, wonders how her friends inside the dome are faring, but things change after she meets handsome Levi Addison, who offers to show her the world from his airship.
Keywords: Survival -- Fiction; Government, Resistance to -- Fiction; Social classes -- Fiction; Coal mines and mining -- Fiction; Science fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / General; JUVENILE FICTION / Science Fiction